Patterns of referral and waiting times for specialist Child and Adolescent Mental Health Services. Issue 1 (9th February 2017) - Smith, Joanna; Kyle, Richard G.; Daniel, Brigid; Hubbard, Gill
Abstract : Background: During 12‐month period (2012/13) around 21, 480 children and young people (CYP) were referred to Child and Adolescent Mental Health Service (CAMHS) in Scotland (NHS Scotland, 2013, Child and Adolescent Mental Health Services waiting times in Scotland). At the end of September 2012, there were 3, 602 CYP still waiting for 'start of treatment' or 'removal from the waiting list', 375 (10%) CYP had waited over 26 weeks and 1, 204 (33%) CYP had waited over 18 weeks (NHS Scotland, 2013, Child and Adolescent Mental Health Services waiting times in Scotland). Referral source, referral reason and the sociodemographic characteristics of CYP are not routinely collected, and therefore, associations between these factors and wait times for 'start of treatment' or 'removal from the waiting list' (i.e. the referral outcome) are unknown. Method: In this exploratory study, a retrospective analysis of referral data was conducted in one CAMHS. Data for 476 referrals between 1st May 2013 and 31st May 2014 were initially analysed to define categories for each of the following key variables: referral source, referral reason and referral outcome. Data on CYP sociodemographic characteristics were extracted from referral records, including age, gender and postcode, from which Scottish Index of Multiple Deprivation quintile of residence was derived. Descriptive statistics were calculated for referral source, referral reason and CYP sociodemographic characteristics. Regression models were then built to determine predictors of a referral being rejected by CAMHS and waiting time for referrals accepted by CAMHS. Data were analysed in SPSS (Version 20). Results: Of the 476 referrals, 72% ( n  = 342) were accepted and 12% (n = 59) were rejected. Most referrals were made by general practitioners. Just under a third of referrals to CAMHS (31%) were for CYP with emotional and behavioural difficulties. The odds of being rejected by CAMHS were significantly higher if referred by teachers and for CYP with emotional and behavioural difficulties. Age and referral reason were significant independent predictors of waiting time after referral to CAMHS, with CYP referred for hyperactivity/inattention waiting significantly longer. Conclusions: Policymakers should consider ways to foster dialogue and collaboration between different groups of professionals making and accepting referrals to CAMHS in order to improve timely access to appropriate mental health support services for CYP. Research is urgently needed to investigate the experiences of CYP who are either rejected by CAMHS or wait lengthy periods of time before starting their treatment with CAMHS.